Efektivitas Video Edukasi Ergonomi terhadap Pengetahuan Pegawai Perkantoran di Sub Subtansi Tata Kelola Pelayanan Kesehatan Dinas Kesehatan Provinsi Jawa Timur - Lutfiyah Azizah, Elisa; Rosyida Ro’is , Rachmy (Universitas Insan Budi Utomo, 2024)
The K3 program is very important to implement in the workplace because every worker is always faced with potential dangers originating from work and/or the work environment which is at risk of causing work accidents and work-related diseases. Improper body position while working can cause various health problems. However, many employees in office environments do not fully understand the importance of implementing ergonomics. This is due to the lack of education or promotion regarding ergonomics in the workplace. Effective health promotion media has an important role in conveying information about office ergonomics. The aim of this research is to evaluate the effectiveness of various health promotion media in increasing employee knowledge about office ergonomics in this work environment. Providing education using video media regarding ergonomics can provide an overview of the most appropriate and effective promotional methods. This research method is Pre Experimental with one group pre-test and post-test design. Next, intervention was given using educational video media related to ergonomics.